2013
DOI: 10.5339/gcsp.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish model system in cardiovascular research: A tiny fish with mighty prospects

Abstract: The zebrafish Danio rerio, a tropical freshwater fish, belongs to the family of cyprinidae, which in the last 30 years has developed into a very popular model organism for studies of embryonic development and human diseases. Initially the zebrafish species has been selected on the basis of its small size of approximately 3-5 cm, its transparency during development and its high fertility, qualities first identified by George Stresinger, the founding father of zebrafish research [1]. The ability to house thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 185 publications
(177 reference statements)
0
57
0
Order By: Relevance
“…We found that, at 52 hpf, less than 10 cells per heart serve as activation origins. They are located in the sinus venosus at the heart's inflow, which is a homologue of the cardiac pacemaker region in adult heart 12 . Our data further shows that the ring-like arrangement of pacemaker cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that, at 52 hpf, less than 10 cells per heart serve as activation origins. They are located in the sinus venosus at the heart's inflow, which is a homologue of the cardiac pacemaker region in adult heart 12 . Our data further shows that the ring-like arrangement of pacemaker cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For study of various heart models such as heart development, heart muscle growth, endocardium and valves development, cardiac conduction system, cardiac electro-physiology, heart regeneration zebra ish models haves been used (Poon and Brand, 2013) . They are used for study of a wide variety of cardiovascular disease processes which includes congenital heart defects, arrhythmia, cardiomyopathy, aortic coarctation.…”
Section: Cardiac Diseasementioning
confidence: 99%
“…PHZ was used at a concentration of 1.25 lg/mL the first week followed by 2.5 lg/mL for the rest of the protocol. Treatment phases were followed by 1 30 min rinsing and washing in fish water. The control group followed the same process without the addition of PHZ in the fish water.…”
Section: Zebrafish and Cardiomyopathy Modelmentioning
confidence: 99%
“…1 The transparency of zebrafish embryos allows observation of the heart and vasculature so that heart morphology and function can be easily analyzed. In addition, the ease of genetic manipulation makes them an incredible tool to identify novel cardiovascular disease genes and decipher pathways leading to congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%